2009
DOI: 10.1021/jp904251j
|View full text |Cite
|
Sign up to set email alerts
|

Tetrapeptide-Based Hydrogels: for Encapsulation and Slow Release of an Anticancer Drug at Physiological pH

Abstract: Here, we report two synthetic oligopeptide-based, thermoreversible, pH-sensitive hydrogels. In gel phase, these self-assembling tetrapeptides form a long interconnected nanofibrilar network structure, as is evident from various microscopic techniques, including field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM). FTIR, circular dichroism, and wide angle X-ray diffraction (WAXD) favor an antiparallel beta-sheet structure of these gelato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 61 publications
3
131
0
Order By: Relevance
“…A sharp peak at 1688 cm −1 clearly suggests the presence of an antiparallel β-sheet arrangement of the gelator peptide molecules within the gel phase material. 13 X-ray Diffraction Studies. To gain insight about the molecular arrangement within the supramolecular network structure, SAXS on gels and wide-angle powder XRD of the xerogel were carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sharp peak at 1688 cm −1 clearly suggests the presence of an antiparallel β-sheet arrangement of the gelator peptide molecules within the gel phase material. 13 X-ray Diffraction Studies. To gain insight about the molecular arrangement within the supramolecular network structure, SAXS on gels and wide-angle powder XRD of the xerogel were carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this study, d = 4.92 Å is the distance between the peptide chains within a β-sheet, while the d spacing of 8.44 Å can be characterized as the distance between two stacked β-sheets. 13 Another peak at d = 3.76 Å signifies the π−π interaction between the phenyl rings of the molecules in the three-dimensional network structure ( Figure 3). 56 Combining these results obtained from X-ray diffraction and FT-IR analyses, it can be concluded that the gelator peptide molecules are self-assembled in the gel state to form a β-sheet-like structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that the diffusion of Dox molecules from the hydrogel is governed by electrostatic, p-stacking and hydrophobic interactions. Furthermore, Dox molecules were previously released from Phe containing hydrophobic peptides that may also be attributed to hydrophobic and p-stacking interactions [37].…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, in the case of neural stem cells, RADA16-I peptide nanofiber scaffold has comprehensively been compared with the most commonly used scaffolds, including PLLA, PLGA, PCLA, type I collagen, type IV collagen, and Matrigel, which indicates that RADA16-I peptide nanofiber scaffold represents a new class of functionalized and biologically active nanofiber scaffold. 22 The well-defined nanofiber networks and the characteristics of the high H 2 O content make it a very attractive class of biological nanomaterial. It is favorable for cell adhesion and differentiation.…”
mentioning
confidence: 99%